2021
DOI: 10.1111/mcn.13236
|View full text |Cite
|
Sign up to set email alerts
|

Iodine status of pregnant women living in urban Johannesburg, South Africa

Abstract: Adequate intake of iodine is important during pregnancy because of its essential role in foetal growth and neurodevelopment. Data on iodine status of South African pregnant women are scarce, and the salt reduction policy implemented in 2016 may decrease iodine intake of South Africans. This cross‐sectional study assessed the iodine status of pregnant women residing in urban Johannesburg, South Africa. A total of 250 pregnant women were enrolled into the ‘Nutrition during Pregnancy and Early Development’ (NuPED… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
0
2
1
Order By: Relevance
“…A similar decrease in UIC and T3 throughout pregnancy was observed in a study of 215 pregnant women in China, although TSH was found to have a U-shaped curve with gestational age [ 73 ]. This is in contrast to a study of South African women ( n = 562) that found UIC increase in each trimester (133 μg/L, 145 μg/L, and 156 μg/L) [ 74 ]. Another study completed in Turkey measured newborn UIC and found 51% of newborns were I deficient [ 75 ].…”
Section: Iodine and Thyroid Function In Pregnancycontrasting
confidence: 99%
See 1 more Smart Citation
“…A similar decrease in UIC and T3 throughout pregnancy was observed in a study of 215 pregnant women in China, although TSH was found to have a U-shaped curve with gestational age [ 73 ]. This is in contrast to a study of South African women ( n = 562) that found UIC increase in each trimester (133 μg/L, 145 μg/L, and 156 μg/L) [ 74 ]. Another study completed in Turkey measured newborn UIC and found 51% of newborns were I deficient [ 75 ].…”
Section: Iodine and Thyroid Function In Pregnancycontrasting
confidence: 99%
“… Siro et al. [ 74 ] Observational South Africa Iodized salt fortification program is in use, but salt reduction legislation has decreased intake N/A Increased UIC throughout pregnancy. Vural et al.…”
Section: Iodine and Offspring Neurodevelopmentmentioning
confidence: 99%
“…In a 2022 observational study in Turkey in a marginally iodine sufficient population, UIC decreased throughout pregnancy with a concomitant increase in TSH, which remained within normal limits, but was associated with a decrease in T3 and T4 [49]. A 2021 observational study in an iodine-sufficient population in rural China found a similar decrease in UIC and T3 throughout pregnancy, but a U-shaped curve with TSH [50], while a 2020 observational study in South Africa with a salt iodization program in place found an increase in UIC throughout pregnancy [51].…”
Section: Iodine and Thyroid Functionmentioning
confidence: 99%